2003
DOI: 10.1136/oem.60.4.279
|View full text |Cite
|
Sign up to set email alerts
|

Neurobehavioural effects among workers occupationally exposed to organophosphorous pesticides

Abstract: Aims: To identify neurobehavioural deficits among workers exposed to organophosphorous (OP) pesticides in their occupation. Methods: This study was conducted during the period when pesticides were applied to cotton crops in the fields in Menoufiya Governorate, Egypt. Fifty two occupationally exposed male workers were compared to 50 unexposed male controls who were similar in age, socioeconomic class, and years of education (>12 years). All participants completed a questionnaire (assessing personal, occupationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
150
2
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 178 publications
(167 citation statements)
references
References 26 publications
14
150
2
1
Order By: Relevance
“…OPs and carbamates act as anti-cholinesterase (anti-ChE) agents. Because of the specificity of this relationship, depression of ChE activity has been used as a biomarker of exposure to these classes of pesticides with few reports on humans (Ohayo-Mitoko et al 2000;Nielsen and Andersen 2002;Farahat et al, 2003;Fenske et al, 2005). There is relatively little research on Ghanaian workers occupationally exposed to OP and carbamate pesticides.…”
Section: Occupational Exposure To Pesticides: Blood Cholinesteraseintmentioning
confidence: 99%
“…OPs and carbamates act as anti-cholinesterase (anti-ChE) agents. Because of the specificity of this relationship, depression of ChE activity has been used as a biomarker of exposure to these classes of pesticides with few reports on humans (Ohayo-Mitoko et al 2000;Nielsen and Andersen 2002;Farahat et al, 2003;Fenske et al, 2005). There is relatively little research on Ghanaian workers occupationally exposed to OP and carbamate pesticides.…”
Section: Occupational Exposure To Pesticides: Blood Cholinesteraseintmentioning
confidence: 99%
“…A study of sheep farmers with longterm exposure to organophosphates found subtle peripheral neuropathy (Beach et al 1996). Fifty-two male workers occupationally exposed to organophosphate pesticides for at least 3 years were compared with 50 unexposed male controls; the pesticide applicators performed worse on tests that measured visuomotor speed, verbal abstraction, attention, and memory (Farahat et al 2003). These studies suggest evidence of neurologic deficits in workers who were occupationally exposed to organophosphate pesticides.…”
mentioning
confidence: 94%
“…There are more than 1000 active ingredients, which are marketed as pesticides [1], and developing countries use 25% of the annual global consumption [2]. In Tanzania, a total of 300 active ingredients were registered and used by 2006 [3], including endosulfan, which is restricted by the Stockholm Convention due to its environmental persistence and the documented toxic potential [4].…”
Section: Introductionmentioning
confidence: 99%